Pattern of obstetrics complication among pregnant females admitted in a tertiary care centre in central India - Shirpurkar, Manik S.; Shewte, Mamta K.; Joshi, Prajkta G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: About half a million women die every year of causes related to pregnancy and child birth. Complication can arise at any time during pregnancy; child birth and post natal period and in absence of intervention, there is a high feto - maternal morbidity and mortality. The aim was to study the pattern of obstetrics complication among antenatal patients coming to a tertiary care centre. Methods: A cross sectional study was conducted among 102 antenatal women admitted in intensive care unit of our institute during July 2014 to November 2014. Data regarding maternal socio-demographic profile and antenatal profile was collected. Results: Total 102 women included in the study. 95 (93%) were registered and 7 were unregistered women. 88 (86.4%) women had 3 or more antenatal visit, of which 3 (2.9%) were unregistered women. 82 (80.3%) women had blood Hb% <11; of which 7 (6.8%) were unregistered women. Out of total 102 women, 64 (62.7%) women were having complications related to abnormal labour; 34 (33.3%) obstetrical disorder, 21 (20.5%) hypertensive disorder. Because of multi-disciplinary team approach at our institute, no maternal mortality was reported among the antenatal women admitted during this period in our institute. Conclusions: All women need access to antenatal care; institutional delivery and post- partum care. Complication arises at any time in absence of intervention. Multidisciplinary team approach along with intensive care specialist and anaesthesiologists can bring optimum care and thereby help in reducing maternal mortality.